A New Focus on Cityscapes in Late Medieval German Literature: Rudolf von Ems and Heinrich Kaufringer. (May 2023) - Classen, Albrecht
Historians have studied the medieval city from many different perspectives already, and even literary historians have endeavoured to identify the evidence in fictional texts pertaining to urban spaces and figures. In many cases, however, the cities as they emerge before our eyes are rather imaginary or dream-like, and lack in historical specificity. This situation changed, as this article demonstrates, with the case of Rudolf von Ems's Der guote Gêrhart (ca. 1220) and the verse narratives by Heinrich Kaufringer (ca. 1400). This study examines the data we can cull from both sides and presents it as the crucial indicator for the emergence of a new literary discourse dedicated to the world of late medieval cities. We begin to discover, though not yet in any consistent way, the formation of urban protagonists and of narrative contexts that are predicated on urban settings.